DIPLOMASI INDONESIA DALAM UPAYA MENINGKATKAN WISATAWAN ASAL VIETNAM TAHUN 2019-2023 - Ambarsari, Ningrum; Dharmawan, Riznalmira (Moestopo Journal of International Relations (MJIR), 2023)
Tourism has emerged as a strategic instrument of diplomacy, facilitating mutual understanding between nations through cultural, historical, and architectural appeal. The bilateral relationship between Indonesia and Vietnam, established since 1955 and strengthened through a tourism cooperation agreement in 1994, provides the foundation for Indonesia’s public diplomacy efforts in promoting tourism to Vietnamese audiences. The COVID-19 pandemic severely impacted global tourism, with a notable decline in Vietnamese visitors to Indonesia in 2020–2021. This research examines how Indonesia leveraged public diplomacy, nation branding, and multi-track diplomacy to revitalize tourist arrivals from Vietnam during 2019–2023. Utilizing a descriptive qualitative method based on document analysis and official statistical data, the study finds that Indonesia’s tourism diplomacy, especially through familiarization trips, international expos, and bilateral engagements, contributed to the gradual recovery of Vietnamese tourist arrivals despite pandemic-related challenges. The findings highlight the effectiveness of adaptive diplomatic strategies in enhancing Indonesia’s tourism sector resilience and fostering closer regional ties.